1195Brain-predicted age difference is associated with cognitive processing and delayed recall in later life. (2nd September 2021) - Wrigglesworth, Jo; Yaacob, Nurathifah; Ward, Phillip; Woods, Robyn; McNeil, John; Storey, Elsdon; Egan, Gary; Murray, Anne; Shah, Raj; Jamadar, Sharna; Trevaks, Ruth; Ward, Stephanie; et al.
Abstract: Background: Brain age is a novel neuroimaging-based marker of ageing that uses machine learning to predict a person's biological brain age. A higher brain age relative to chronological age (i.e., brain-predicted age difference [brain-PAD]) is considered a sign of accelerated ageing. We examined whether brain-PAD is associated with cognition and the change in cognitive function over time. Methods: This study involved 531 cognitively healthy community-dwelling older adults (70+ years). Using a previously trained algorithm, brain age was estimated using T1-weighted structural magnetic resonance images acquired at baseline. Psychomotor speed, delayed recall, verbal fluency and global cognition were assessed at baseline, years 1 and 3. Results: At baseline, a significant negative association was observed between brain-PAD and psychomotor speed (r=-0.14, p = 0.001), delayed recall (r=-0.09, p = 0.04), and the three-year change in delayed recall (r=-0.15, p = 0.02), which persisted after adjusting for covariates. Conclusions: These findings indicate that accelerated brain ageing in cognitively unimpaired older people is associated with worse psychomotor speed, and delayed recall. This study also provides new evidence that accelerated brain ageing is a risk factor for progressive memory decline. Future research would benefit from further prospective analyses of associations between brain-PAD and cognitive function in community dwelling older adults. Key messages: Brain age is a neuroimaging-based marker of biological ageing. A higher estimate of brain age relative to chronological age (i.e., accelerated ageing) is associated with worse psychomotor speed and memory, and memory decline.